A Multicenter, Prospective, Noninterventional Study in a Norwegian Cohort of Patients with Moderate-to-Severe Allergic Rhinitis Treated with MP-AzeFlu. Issue 3 (October 2017) - Dollner, Ralph; Larsen, Petter Lorentz; Dheyauldeen, Sinan; Steinsvåg, Sverre
Background: Allergic Rhinitis and its Impact on Asthma guidelines recently recommended a treatment strategy for allergic rhinitis (AR) based on disease control rather than symptom severity by using a visual analog scale (VAS) to categorize control Objectives: To evaluate the effectiveness of MP-AzeFlu (Dymista ® ) by using this VAS in routine clinical practice in Norway. MP-AzeFlu comprises a novel formulation that contains azelastine hydrochloride, fluticasone propionate and excipients delivered in a single spray. Methods: This multicenter, prospective, noninterventional study enrolled patients (n = 160) with moderate-to-severe AR and acute symptoms who were eligible to receive treatment with MP-AzeFlu according to its summary of product characteristics. Patients assessed symptom severity by using a VAS from 0 (not at all bothersome) to 100 mm (very bothersome) in the morning before MP-AzeFlu use on days 0, 1, 3, 7, and after 14 days. On day 3, the patients assessed their level of disease control as well controlled, partly controlled, or uncontrolled. The proportion of Norwegian patients who achieved defined VAS score cutoffs for "well-controlled" and "partly controlled" AR were also calculated. Results: MP-AzeFlu reduced the mean ± standard deviation VAS score from 68.1 ± 16.4 mm at baseline to 37.4 ± 25.9 mm on the last day, a reduction of 30.8 ± 27.2 mm. The results were consistent, irrespective of disease severity, phenotype (i.e., seasonal AR [SAR], perennial AR [PAR], SAR plus PAR, unknown) or age (i.e., 12–17, 18–65, and >65 years). Of the patients (with recorded data), 88.1% considered their symptoms to be partly or well controlled at day 3; and 19.5, 32.0, 50.0, and 61.0% of the patients achieved a ≤38 mm well-controlled VAS score cutoff on days 1, 3, 7, and the last day, respectively. Conclusions: MP-AzeFlu provided rapid sustained symptom control in a routine clinical practice in Norway, which provided support for its effectiveness for the treatment of AR in real life.